2020
DOI: 10.1101/2020.04.14.041772
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expanding the space of protein geometries by computational design ofde novofold families

Abstract: Naturally occurring proteins use a limited set of fold topologies, but vary the precise geometries of structural elements to create distinct shapes optimal for function. Here we present a computational design method termed LUCS that mimics nature’s ability to create families of proteins with the same overall fold but precisely tunable geometries. Through near-exhaustive sampling of loop-helix-loop elements, LUCS generates highly diverse geometries encompassing those found in nature but also surpassing known st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 31 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…Baker group has shown that deep ResNet can fold 16 of the 18 de novo proteins designed by the same group [12]. Here we conduct a more comprehensive study on 21 de novo proteins designed by two research groups in 2018-2020 [26][27][28], among which 11 proteins have been used to test trRosetta. None of these 21 proteins has evolutionarily related homologs in the 2018 Cath S35 training proteins (HHblits with E-value<0.1).…”
Section: Folding Proteins Without Co-evolution Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Baker group has shown that deep ResNet can fold 16 of the 18 de novo proteins designed by the same group [12]. Here we conduct a more comprehensive study on 21 de novo proteins designed by two research groups in 2018-2020 [26][27][28], among which 11 proteins have been used to test trRosetta. None of these 21 proteins has evolutionarily related homologs in the 2018 Cath S35 training proteins (HHblits with E-value<0.1).…”
Section: Folding Proteins Without Co-evolution Informationmentioning
confidence: 99%
“…We collected 35 de novo proteins (including 7 membrane proteins) designed by two research groups in the past several years. Meanwhile, 4 of them are designed by Kortemme group [28] and the others by Baker group. Among these proteins, 21 of them have HHblits E-value>0.001 with our training proteins in the 2018 Cath S35 dataset, so we only use these 21 proteins as our test set.…”
Section: Independent Test Datamentioning
confidence: 99%
“…Computer-aided de novo protein design is particularly suitable for designing completely novel structures because it allows sampling of a vast sequence space in silico. The resulting designs are often expressed and tested in E. coli (Cao et al, 2020;Glasgow et al, 2019;Pan et al, 2020;Xu et al, 2020). More recently, strategies for evolving mammalian systems have emerged (Berman et al, 2018;English et al, 2019;Piatkevich et al, 2018), although E. coli and yeast remain the preferred hosts for handling large libraries (Almhjell et al, 2018;Branon et al, 2018;Bryson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…2N8I; 177 loop-helix-loop unit combinatorial sampling, or LUCS, from Kortemme's group, e.g. 6VGA; 178 and TopoBuilder from Bruno Correia and colleagues for incorporating functional elements into de novo protein frameworks. 103,105 Gaps and remaining challenges: These advances in computational de novo protein design are allowing increasingly challenging design targets to be addressed such as structures rich in b structure -2KL8, 179 3WW7, 180 5BVL, 172 and 5KPE 181 ; and membrane-spanning peptide and protein assemblies -2MUZ, 106 6B85, 107 6MCT, 108 6M6Z, 84 6X9Z, 109 and 6YB1.…”
Section: Coiled-coil Assemblies As a Special And Particularly Accessi...mentioning
confidence: 99%